Graphene-like materials from biomass using deep eutectic solvents: A review - Zafar, Saima; Cherakkara, Aswathi; Izan Izwan, Misnon; Yang, Chun-Chen; Jose, Rajan (ACS Publications, 2024)
Material sustainability is an ongoing challenge, and their renewable sourcing is the ultimate solution. Graphene-like materials (GLMs) such as graphene, graphene oxide, reduced graphene oxide, graphene quantum dots, and graphite are home to enormous physical and chemical properties exploitable for a range of applications. Lignin, a major component in plant biomass, shares structural similarity with GLMs and, therefore, could be their renewable source. The focus of this work is on the methods employed for the extraction of lignin from biomass using deep eutectic solvents (DESs). DESs have proven to be efficient in the isolation of lignin, presenting a sustainable pathway for the production of GLMs. Results from various studies are presented to demonstrate how lignin can be converted to GLMs. The implications of these findings extend beyond material sustainability and include applications in various fields, such as electronics and energy storage devices. This Review not only addresses the existing knowledge but also contributes to the advancement of ecofriendly methodologies in the pursuit of GLMs, thereby fostering material sustainability.